Identification and Functional Characterization of Anti-metastasis and Anti-angiogenic Activities of Triethylene Glycol Derivatives - Oh, Eonju; Garg, Sukant; Liu, Ye; Afzal, Sajal; Gao, Ran; Yun, Chae-Ok; Kaul, Sunil C.; Wadhwa, Renu (Frontiers in Oncology, 2018)
We had previously reported anticancer activity in the water extract (WEX) of Ashwagandha leaves and identified Triethylene glycol (TEG) as an active tumor suppressor component. In this study, we investigated anti-migratory and anti-angiogenesis activities of WEX and TEG. We conducted in vitro and in vivo experiments using TEG, and its two derivatives, Triethyleneglycol dimethacrylate (TD-10) and Tetraethyleneglycol dimethacrylate (TD-11). The data revealed strong anticancer and anti-metastasis potentials in the derivatives. Non-toxic, anti-migratory doses of the derivatives showed inhibition of canonical Wnt/-catenin axis and consequent downregulation of EMT-signaling proteins (Vimentin, MMPs and VEGF). These results endorse that the TD-10 and TD-11 have potential to safely put a check on the aggressiveness of the metastatic cells, therefore represent promising candidates for the treatment of metastatic cancers.